Islam dan Pendidikan Cinta Damai - Moh. Toriqul Chaer (ISTAWA, 2017)
The nation of Indonesia is the pluralist nation. The plurality suggests the existence of a difference. The understanding and management of plurality would generate a positive force for the development of the nation. On the contrary, when it is not understood and managed properly, the plurality of faiths and cultures can be a destructive factor and trigger a disaster. Conflict and social violence that often occurs between community groups are part of the plurality of religions and cultures that are not managed properly. Religious conflict as happened in Maumere (1995), Surabaya, Situbondo and Tasikmalaya Rengasdengklok (1996), (1997), Solo, Jakarta and Kupang (1998), Poso, Ambon (1999-2002), not only claimed the casualties is not a little, but it has also destroyed hundreds of places of worship (whether a church or Mosque) caught fire and was destroyed. Similarly, notes smelling of ethnic violence, such as certain ethnic violence in West Kalimantan (1933), Central Kalimantan (2000). Necessary preventive measures as early prevention efforts, so that such events do not reoccur in the future. Peace education is an effort bring education more tolerant, understanding the diversity of religions, ethnicities, and cultures.